PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI BERBANTUAN ADOBE PREMIERE PADA MATA PELAJARAN MATEMATIKA UNTUK SISWA KELAS 4 SDN 1 WATES KABUPATEN TULUNGAGUNG - Mohammad Fajar Romadoni; Nourma Oktaviarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low understanding of fourth-grade students at SDN 1 Wates Tulungagung Regency on fraction material in mathematics learning. The problem was caused by the use of conventional learning media that were less interactive and had not optimally utilized digital technology, causing students to feel bored quickly and have difficulty understanding abstract concepts. This study aimed to develop animated video-based learning media assisted by Adobe Premiere for mathematics subjects for fourth-grade students at SDN 1 Wates Tulungagung Regency, determine the validity level of the media based on assessments from material experts and media experts, and determine the practicality level of the developed media. The research method used was Research and Development (R&D). Data collection techniques were conducted through observation, interviews, material expert and media expert validation questionnaires, as well as teacher and student response questionnaires. The material expert validation results obtained a percentage of 89% categorized as very valid, while the media expert validation results obtained a percentage of 90.7% categorized as very valid. The practicality test results showed a percentage of 90.62% categorized as very practical. Therefore, the animated video learning media assisted by Adobe Premiere is feasible to be used in teaching fraction material in elementary school mathematics learning